KADAR ESTROGEN DAN PROFIL OVIDUK PUYUH (Coturnix coturnix japonica) SETELAH PEMBERIAN CAHAYA MONOKROMATIK - Kasiyati, Kasiyati; Kusumorini, Nastiti; Maheshwari, Hera; Manalu, Wasmen (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Light plays an important role in the avian life. The present study was designed to evaluate the effects of monochromatic light on serum estrogen concentrations and profile the oviduct, that were the length and weight of the oviduct in the quail. Two hundred and seventy quails were divided into nine treatments of light, with ten replications and three quails in each replication. The treatments were without light, controls with 15 and 25 W, red, green, and blue lights with intensities of 15 and 25 lux. Control treatment used incandescent bulb. The red, green, and blue lights were provided by light emitting diodes (LED). All lights treatment were given for 14 h daily, started from 17.00 to 07.00. Parameters measured were serum estrogen concentrations, and weights and lengths of the oviduct on weeks 5, 7, and 9. Quails exposed to monochromatic light had higher serum estrogen concentrations (P<0,05). Quails exposed to monochromatic light had better weights and lenghts of the oviduct development. Blue light could be used to increase serum estrogen concentrations and stimulate shell gland development.